1996
DOI: 10.1002/(sici)1097-0290(19960120)49:2<111::aid-bit1>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the fluxes in the central metabolism of Corynebacterium glutamicum by nuclear magnetic resonance spectroscopy combined with metabolite balancing

Abstract: To determine the in vivo fluxes of the central metabolism we have developed a comprehensive approach exclusively based on the fundamental enzyme reactions known to be present, the fate of the carbon atoms of individual reactions, and the metabolite balance of the culture. No information on the energy balance is required, nor information on enzyme activities, or the directionalities of reactions. Our approach combines the power of 'H-detected 13C nuclear magnetic resonance spectroscopy t o follow individual car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
230
1
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 116 publications
(245 citation statements)
references
References 0 publications
12
230
1
2
Order By: Relevance
“…This implies the in vivo activity of NADPH consuming reactions. Similar findings were reported for the lysine producing strain C. glutamicum MH 20±22 B [6]. Possible candidates pointed out by the authors were in vivo NADPH regeneration by an oxidase, malic enzyme or alternative reactions, which have not been identified yet.…”
supporting
confidence: 86%
See 3 more Smart Citations
“…This implies the in vivo activity of NADPH consuming reactions. Similar findings were reported for the lysine producing strain C. glutamicum MH 20±22 B [6]. Possible candidates pointed out by the authors were in vivo NADPH regeneration by an oxidase, malic enzyme or alternative reactions, which have not been identified yet.…”
supporting
confidence: 86%
“…13 C tracer experiments with MALDI-TOF MS (this paper), NMR [6], and metabolite balancing [17] lead to similar conclusions concerning the metabolism of C. glutamicum during lysine production. This supports the consistency of the applied techniques.…”
Section: O N C L U S I O N Smentioning
confidence: 53%
See 2 more Smart Citations
“…In principle, NADPH can be synthesized in C. glutamicum by the enzymes of the oxidative pentose phosphate pathway (PPP), glucose-6-phosphate dehydrogenase and 6-phosphogluconate dehydrogenase (Moritz et al 2000), by isocitrate dehydrogenase (Eikmanns et al 1995) and by malic enzyme (Gourdon et al 2000). Carbon flux analysis revealed that during growth on glucose, NADPH for lysine biosynthesis is provided by the PPP, whereas isocitrate dehydrogenase and malic enzyme are of minor importance (Marx et al 1996(Marx et al , 1997(Marx et al , 1999. During growth of C. glutamicum on fructose or on fructose/glucose mixtures, a low carbon flux through the oxidative PPP was demonstrated (Dominguez et al 1998;Kiefer et al 2004;Pons et al 1996).…”
Section: Introductionmentioning
confidence: 99%